2022
DOI: 10.1111/cod.14056
|View full text |Cite
|
Sign up to set email alerts
|

Allergic contact dermatitis caused by 2‐hydroxyethyl methacrylate and ethyl cyanoacrylate contained in cosmetic glues among hairdressers and beauticians who perform nail treatments and eyelash extension as well as hair extension applications: A systematic review

Abstract: Current cosmetic regulations primarily focus on protecting consumers, not the professional user who is subjected to a partly different, and certainly more intense exposure to hazardous substances. Against this background, this systematic review aims to compile and appraise evidence regarding skin toxicity of 2‐hydroxyethyl methacrylate (HEMA; CAS no. 212‐782‐2) and ethyl cyanoacrylate (ECA; CAS no. 7085‐85‐0) contained in cosmetic glues used among hairdressers and beauticians who perform nail treatments and ey… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
26
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 32 publications
(33 citation statements)
references
References 72 publications
1
26
0
Order By: Relevance
“…Being a trained beautician and having had a positive patch-test to acrylates were significantly associated with ANMS-related hand eczema, specifically. This correlates with a recent systematic review, which showed a 9-fold increased risk of HEMA-allergy in hairdressers and beauticians, compared with controls who were not employed in these professions ( 19 ). Thus, an occupational risk of contact allergy to HEMA seems evident in a population of hairdressers, especially in those who also train as beauticians, which may correlate with a higher exposure to ANMS compared with normal users.…”
Section: Discussionsupporting
confidence: 89%
“…Being a trained beautician and having had a positive patch-test to acrylates were significantly associated with ANMS-related hand eczema, specifically. This correlates with a recent systematic review, which showed a 9-fold increased risk of HEMA-allergy in hairdressers and beauticians, compared with controls who were not employed in these professions ( 19 ). Thus, an occupational risk of contact allergy to HEMA seems evident in a population of hairdressers, especially in those who also train as beauticians, which may correlate with a higher exposure to ANMS compared with normal users.…”
Section: Discussionsupporting
confidence: 89%
“…Results concerning the two "cosmetic glues" considered, 2-hydroxyethyl methacrylate and ethyl cyanoacrylate, have been published separately. 9 Very often, more than one of the target substances has been examined in study reports, except for PPD, usually tested as part of a baseline series, which only exceptionally includes other agents within our scope. 2-Methoxymethyl-p-phenylenediamine has only been tested selectively, mostly in PPD-sensitized patients, to examine the degree of cross-elicitation.…”
Section: Resultsmentioning
confidence: 99%
“…30 These substances can cause skin and eye irritation, contact dermatitis, nail detachment, and paronychia. 31,32 In a retrospective study on the frequency of ACD by nail care products using North American Contact Dermatitis Group data, 13 the top five allergens related to nail care products were 2-hydroxyethyl methacrylate (2-HEMA) (56.6%), tosylamide (36.2%), MMA (27.8%), ethyl acrylate (EA) (25.2%), and ethyl cyanoacrylate (6.9%). These substances are a part of the adhesive components in nail beauty products, and individuals allergic to them may develop dermatitis of hands and fingers, but also ectopic dermatitis (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…The main substances used as adhesives in nail care products are mostly based on mixtures of alcohols and cyanoacrylates or methacrylates and resins (polyester, epoxies, polyurethanes, and silicon) 30 . These substances can cause skin and eye irritation, contact dermatitis, nail detachment, and paronychia 31,32 . In a retrospective study on the frequency of ACD by nail care products using North American Contact Dermatitis Group data, 13 the top five allergens related to nail care products were 2‐hydroxyethyl methacrylate (2‐HEMA) (56.6%), tosylamide (36.2%), MMA (27.8%), ethyl acrylate (EA) (25.2%), and ethyl cyanoacrylate (6.9%).…”
Section: Discussionmentioning
confidence: 99%